Pre-vaccination inflammation and B-cell signalling predict age-related hyporesponse to hepatitis B vaccination - Fourati, Slim; Cristescu, Razvan; Loboda, Andrey; Talla, Aarthi; Filali, Ali; Railkar, Radha; Schaeffer, Andrea K.; Favre, David; Gagnon, Dominic; Peretz, Yoav; Wang, I-Ming; Beals, Chan R.; et al. (Nature communications, 2016)
Aging is associated with hyporesponse to vaccination, whose mechanisms remain unclear. In this study hepatitis B virus (HBV)-naive older adults received three vaccines, including one against HBV. Here we show, using transcriptional and cytometric profiling of whole blood collected before vaccination, that heightened expression of genes that augment B-cell responses and higher memory B-cell frequencies correlate with stronger responses to HBV vaccine. In contrast, higher levels of inflammatory response transcripts and increased frequencies of pro-inflammatory innate cells correlate with weaker responses to this vaccine. Increased numbers of erythrocytes and the haem-induced response also correlate with poor response to the HBV vaccine. A transcriptomics-based pre-vaccination predictor of response to HBV vaccine is built and validated in distinct sets of older adults. This moderately accurate (area under the curve≈65%) but robust signature is supported by flow cytometry and cytokine profiling. This study is the first that identifies baseline predictors and mechanisms of response to the HBV vaccine. Ageing is associated with poor responses to vaccines but the underlying mechanism remains unclear. Here the authors use a systems-based approach to define molecular signatures present before vaccination that correlate with non-responsiveness to hepatitis B vaccination in healthy, elderly adults.